Sexuality-Free Careers? Sexual Minority Young Adults' Perceived Lack of Labor Market Disadvantages. (2nd May 2017) - Ueno, Koji; Peña-Talamantes, Abráham E; Roach, Teresa; Nix, Amanda N; Ritter, Lacey J
Abstract: In recent studies, many young sexual minorities reported that their minority status has not undermined their career plans, despite the persistent heteronormativity in schools, workplaces, and family. By analyzing in-depth interviews of 34 sexual minority young adults, this article examines how they develop such a perception. Their explanations included five elements—distancing themselves from sexual minorities who conformed to stereotypes about the group, overlooking career sacrifices they had already made, anticipating that their future careers would be sexuality free, and maintaining a general sense of hope and optimism. Some respondents even anticipated positive career consequences, pointing to three advantages of sexual minority status, including a strong career motivation, unique skills and abilities, and favorable treatments from employers. We interpret these results by conceptualizing their career plans as a part of their life narratives and discuss the implications for the sexual minority population and for society.